Metaphorical Representation of Future in British Political Discourse - Solopova, Olga A. (Respectus Philologicus, 2005)
The present paper is concerned with metaphors used to create the image of the future in the British political discourse “General Election-2001”. The analysis focuses on a) some metaphors used to create the image of the future and its periods (“near future” - “distant future”), b) frequency of metaphorical models used to create the image of future and its periods, and e) correlation of metaphorical representations of future and its periods. The research is based on the cognitive linguistic theory of metaphor first expounded by G. Lakoff but also draws useful insights from other explorations dealing with the prospective function of political discourse (D. Graber, E. Lassan, A . Chudinov, T. Shmeleva, etc.). The conclusion is that the most frequent metaphor models used in portraying the “near future” are war, disease and family relationships in conceptualising the “distant future”– journey, architecture and disease. The results of the study show that the metaphorical representation of the future is that the mass media and politicians use frequent and efficient means in the British political discourse “General Election-2001“.